PENGARUH PRAKTIK GREEN ACCOUNTING DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN: PERAN MODERASI PROFITABILITAS DI SEKTOR KESEHATAN - Dwi Sivia Handayani; Cicilia Erly Istia (Politeknik Negeri Malang, 2026)
This study analyzes the effects of green accounting practices and environmental performance on firm value, with profitability as a moderating variable in the healthcare sector. The focus on this sector is based on the urgency of managing specific environmental impacts in the healthcare industry. Using a quantitative approach, this study focused on five healthcare sector issuers on the Indonesia Stock Exchange (IDX) for the 2018-2023 period. Total of 30 observations were collected through purposive sampling criteria and analyzed using Moderated Regression Analysis (MRA) with SPSS 26. The results indicate that environmental performance has a significant positive effect on firm value. However, green accounting practices did not show a significant effect, and profitability was unable to moderate the relationship between these variables and firm value.